An instrument to collect data on frequency and intensity of symptoms in older palliative cancer patients: A development and validation study. (April 2016) - Van Lancker, Aurélie; Beeckman, Dimitri; Verhaeghe, Sofie; Van Den Noortgate, Nele; Grypdonck, Mieke; Van Hecke, Ann
Abstract: Purpose: To develop and validate an instrument to collect data on symptoms (frequency/intensity) in older palliative cancer patients. Methods: A four-phase instrument development and validation study was performed. A preliminary version of the instrument was developed through a literature review. Face- and content validity were assessed in a Delphi-procedure with eleven experts. Cognitive interviewing with 24 older cancer patients was performed to enhance content validity of the instrument. Test–retest was performed to assess the stability. Results: An 40-item instrument was developed. The Assessment Symptoms Palliative Elderly (ASPE) collects data on frequency and intensity of 24 physical, 10 psychological, 3 functional, 1 spiritual and 2 social symptoms. Content validity was excellent (I-CVI 81.8%–100.0% and S-CVI 92.9%). Cognitive interviewing allowed to improve the content validity. Test–retest showed substantial to almost perfect agreement for 87.5% of the items. No item had poor or fair agreement. Conclusion: This study resulted in the development of the ASPE which reflects good properties for face- and content validity and reliability. Cognitive interviewing has a valuable contribution in the validation process. The instrument can be used to gain insight in symptoms in older palliative cancer patients. Highlights: A new symptom assessment instrument in older palliative cancer patients is proposed. The new instrument reflects good face- and content validity and reliability. Cognitive interviewing has a valuable contribution in the validation process.